2022
DOI: 10.1016/j.jbc.2022.101587
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of DNA-binding activity of the Staphylococcus aureus catabolite control protein A by copper (II)-mediated oxidation

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…Several studies have shown significant changes in carbon source acquisition, central metabolism, and PTS gene expression in the presence of copper, as well as the fixation of mutants in PTS genes during experimental evolutionary studies on copper resistance (Quesille-Villalobos et al 2019 , Boyd et al 2022 , Dao et al 2023 ). Copper signaling has also been demonstrated to regulate the DNA-binding activity of CcpA in Staphylococcus aureus (Liao et al 2022 ), and excess copper in the environment has been shown to increase the catabolic diversity of Gram-positive bacteria (Yang et al 2022 ). To determine whether copper toxicity was ameliorated by the PTS system in E. faecium , we propagated the WT and ∆ ptsHI strains in rich media containing 0-16 mM copper (CuSO 4 ) (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have shown significant changes in carbon source acquisition, central metabolism, and PTS gene expression in the presence of copper, as well as the fixation of mutants in PTS genes during experimental evolutionary studies on copper resistance (Quesille-Villalobos et al 2019 , Boyd et al 2022 , Dao et al 2023 ). Copper signaling has also been demonstrated to regulate the DNA-binding activity of CcpA in Staphylococcus aureus (Liao et al 2022 ), and excess copper in the environment has been shown to increase the catabolic diversity of Gram-positive bacteria (Yang et al 2022 ). To determine whether copper toxicity was ameliorated by the PTS system in E. faecium , we propagated the WT and ∆ ptsHI strains in rich media containing 0-16 mM copper (CuSO 4 ) (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Sugar-specific PTS or the universal enzymes PtsI and PtsH have been demonstrated to be involved in regulatory processes involving carbon through carbon catabolite repression (CCR), both independently and as a co-repressor with the catabolite control protein (CcpA). A role in nitrogen, and phosphate metabolism; chemotaxis; potassium transport; cold shock response; hydrogen peroxide resistance; biofilm formation; and virulence has also been demonstrated in multiple species (Graumann et al 1996 , Kok et al 2003 , Phadtare 2004 , Beaufils et al 2007 , Monedero et al 2007 , Houot and Watnick 2008 , Houot et al 2010a , b , Le Bouguenec and Schouler 2011 , Zhang et al 2013 , Gera et al 2014 , Derkaoui et al 2016 , Paganelli et al 2016 , Peng et al 2017 , Gao et al 2018 , Horng et al 2018 , Bier et al 2020 , Liao et al 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…Simultaneously, the up-regulated repressor regulating gene arsR also contributed to the decrease of bacterial As, and the down-regulated metal chaperone copZ could help to decrease Cu homeostasis system of MSRA (fig. S24) ( 55 , 58 ). This may be due to the attack of ROS, NO, and ONOO − on iron-sulfur cluster proteins and copper binding cytoplasmic proteins in the tricarboxylic acid cycle enzymes, reducing adenosine 5´-triphosphate (ATP) production (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The formation of intermolecular DBs between LL-37 and bovine serum albumin is believed to stabilize protein nanoparticles that might be used as promising vehicles to deliver therapeutics, otherwise unstable, for the treatments of lung infections from Pseudomonas aeruginosa [17]. Two cysteine residues of the Staphylococcus aureus catabolite control protein A (CcpA) have been shown to be important for resisting human innate immunity, too: they can be oxidized and form an intermolecular DB between two CcpA dimers, with the formation of a tetramer and CcpA dissociation from its cognate DNA promoter [18].…”
Section: Introductionmentioning
confidence: 99%
“…Two cysteine residues of the Staphylococcus aureus catabolite control protein A (CcpA) have been shown to be important for resisting human innate immunity, too: they can be oxidized and form an intermolecular DB between two CcpA dimers, with the formation of a tetramer and CcpA dissociation from its cognate DNA promoter [ 18 ].…”
Section: Introductionmentioning
confidence: 99%